Surface Lipids as Multifunctional Mediators of Skin Responses to Environmental Stimuli - Chiara De Luca; Giuseppe Valacchi (Mediators of Inflammation)
Skin surface lipid (SSL) film is a mixture of sebum and keratinocyte membrane lipids, protecting skin from environment. Its composition is unique for the high percentage of long chain fatty acids, and of the polyterpenoid squalene, absent in other human tissues, and in non-human Primates sebum. Here, the still incomplete body of information on SSL as mediators of external chemical, physical, and microbial signals and stressors is revised, focusing on the central event of the continuous oxidative modification induced by the metabolic activity of residential and pathological microbial flora, natural or iatrogenic UV irradiation, exposure to chemicals and cosmetics. Once alpha-tocopherol and ubiquinol-10 antioxidant defences of SSL are overcome, oxidation of squalene and cholesterol gives rise to reactive by-products penetrating deeper into skin layers, to mediate local defensive inflammatory, photo-protective, immune reactions or, at higher concentrations, inducing local but also systemic immune depression, ultimately implicating skin cancerogenesis. Qualitative modifications of SSL represent a pathogenetic sign of diagnostic value in dermatological disorders involving altered sebum production, like pytiriasis versicolor, acne, atopic or seborrheic dermatitis, as well as photo-aging. Achievements of nutriceutical interventions aimed at restoring normal SSL composition and homeostasis are discussed, as feasible therapeutic goals and major means of photo-protection.